Aging constitutive model of hydroxyl-terminated polybutadiene coating in solid rocket motor. (October 2018) - Li, Ke; Zheng, Jian; Zhi, Jianzhuang; Zhang, Kailun
Abstract: To accurately describe the tensile mechanical properties of aged hydroxyl-terminated polybutadiene (HTPB) coating, the aging constitutive model was studied. The single-step and multi-step relaxation tests were performed on the unaged samples, and the tensile mechanical properties of the aged HTPB coating were tested, while the crosslink density was obtained by nuclear magnetic resonance (NMR) experiments. The model parameters were solved using the experimental data. The crosslink density was used to characterize the aging degree of the HTPB coating, and combined with the modified Arrhenius equation, a model of crosslink density variation with aging time was built. Multiply the hyper-elastic model with the aging characteristic function, an aging constitutive model of HTPB coating was established, which can be used to describe the tensile mechanical properties of aging HTPB coating. The verification tests show that the predicted value of the crosslink density under the test of 313.15 K is in good agreement with the test value. The aging constitutive model can predict the tensile mechanical behavior of HTPB coating well, which is of important engineering significance. Highlights: Building constitutive model by aging properties function and hyper-elastic model. Constitutive model describing tensile properties of material. Considering crosslink density as core factor of aging properties function. Predicting crosslink density by Modified Arrhenius method.